Self-medication in children with upper respiratory diseases in a mother-child center in Peru: Automedicación en niños con enfermedades de vías respiratorias altas en un centro materno infantil en Perú - Cucho Vásquez, Kelly Carolina (2023)
Introduction: Self-medication is a common practice to alleviate symptoms of various diseases in child population such as pharyngitis and rhinopharyngitis that are common in health centers in Peru. Objective: To determine the factors associated with self-medication in children with upper respiratory tract diseases. Material and methods: Cross-sectional analytical observational study. The sample size was 206 parents who went with their children to the Emergency Service. A questionnaire approved by Valenzuela. M and the SPSS program were used to find the frequency, bivariate analysis and multivariate logistic regression analysis of Poisson. Results: The prevalence of self-medication in children was 91.3%. Parents who only studied primary and secondary school were more likely to self-medicate their children APR=1.22 (95% CI: 1.01-1.40). The firstborn were protected from self-medication APR=0.86 (95% CI: 0.76-0.97). Parents who were between 20 and 29 years old obtained APR=1.04 (95% CI: 0.96-1.13), children under 7 years old, APR=0.99 (95% CI: 0.91-1.07) and parents who had 1 child APR=1.04 (95% CI: 0.90-1.20). Conclusions: The educational level and the order number of the child, such as being the firstborn, had a significant association with self-medication in children.